2021
DOI: 10.1038/s41514-021-00068-5
|View full text |Cite
|
Sign up to set email alerts
|

Modeling transcriptomic age using knowledge-primed artificial neural networks

Abstract: The development of ‘age clocks’, machine learning models predicting age from biological data, has been a major milestone in the search for reliable markers of biological age and has since become an invaluable tool in aging research. However, beyond their unquestionable utility, current clocks offer little insight into the molecular biological processes driving aging, and their inner workings often remain non-transparent. Here we propose a new type of age clock, one that couples predictivity with interpretabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 86 publications
(91 reference statements)
1
25
0
Order By: Relevance
“…Deep learning models have been successfully applied to transcriptomic and clinical blood biomarker data for age prediction 14 , 15 . For DNA methylation data, Galkin et al recently showed that a deep neural network model, DeepMAge 16 , gave slightly better prediction performance than Horvath’s model in blood samples.…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning models have been successfully applied to transcriptomic and clinical blood biomarker data for age prediction 14 , 15 . For DNA methylation data, Galkin et al recently showed that a deep neural network model, DeepMAge 16 , gave slightly better prediction performance than Horvath’s model in blood samples.…”
Section: Introductionmentioning
confidence: 99%
“…So far, molecular aging clocks have largely relied on datasets built using bulk tissue input or purified cell populations [9][10][11][12][13][27][28][29][30][31][32][33][34] . Bulk tissue profiles (and even purified populations) average the molecular profiles from many cells, integrating tissue composition changes and celltype-specific responses.…”
mentioning
confidence: 99%
“…In order to present a complete study, a computational regression model whose task was to predict the age of the enamel based on information about its broadly understood structure was built. The proposed model is based on artificial neural networks (ANNs), which are computational models regarded as intelligent systems used to solve complex problems with nonlinear relationships using many independent parameters [ 52 , 62 , 63 , 64 ]. MLP network with 13 inputs, one hidden layer and one output ( Figure 11 ) was used to predict the day of postnatal life based on collected data.…”
Section: Resultsmentioning
confidence: 99%